Efficacy and Safety of Rescue Treatment with Plasma Exchange in Patients with Acute Inflammatory Neurological Disorders: A Single Center Experience - Salvatore Iacono; Giuseppe Schirò; Giuseppe Salemi; Elisabetta Scirè; Paolo Aridon; Michele Melfa; Michele Andolina; Gabriele Sorbello; Andrea Calì; Filippo Brighina; Marco D'Amelio; Paolo Ragonese (MDPI AG, 2024)
Background: Therapeutic plasma exchange (TPE) is a highly effective rescue treatment for patients with acute exacerbation of neuroimmunological disease that removes circulating autoantibodies and inflammatory components from the bloodstream. The aims of this study are to explore the safety and the effectiveness of TPE in patients with autoimmune neurological disorders. Methods: We retrospectively evaluated the frequency of adverse events (AEs) and the effectiveness of TPE using the modified Ranking Scale (mRS) in patients with acute neurological flares who underwent TPE at the University Hospital of Palermo. Results: Of 59 patients, the majority underwent TPE due to multiple sclerosis (MS) relapse. In 23.7% of cases, TPE was performed before obtaining a definite diagnosis due to the severity of the clinical presentation. After TPE, the mRS score was globally reduced (p < 0.0001), and this effect was marked in patients with MS, Guillain-Barré syndrome, and myasthenia gravis crisis but not in those with paraneoplastic syndromes. Circulating pathogenetic antibodies, younger age, and the early use of TPE were factors strongly associated with TPE effectiveness. The overall safety profile of TPE was satisfactory with an AE frequency of 15%. Conclusions: These results highlight the early use of TPE in patients with circulating pathogenetic antibodies as well as its favorable safety profile.